Dietary betaine reduces incidence of follicular cyst in post-partum Karan Fries cows during hot-humid season - RAHEJA, NITIN; KUMAR, NISHANT; LATHWAL, S S (The Indian Journal of Animal Sciences, 2020)
The objective of this study was to investigate the heat stress ameliorating effect of dietary betaine in reducing the risk of development of follicular cyst in dairy cows during hot-humid season. Eighteen pre-parturient Karan Fries (KF) cows in their 2nd to 5th parity were selected and assigned to 2 groups of 9 cows each on basis of parity and body weight. One group of cows was kept as control and other as treatment (50 g betaine/day/cow). Environmental variables and temperature humidity index (THI) of sheds were recorded during the experimental period. Body weight, dry matter intake (DMI), plasma non esterified fatty acids (NEFA) and cortisol levels were measured in both groups at fortnightly interval. Trans-rectal B-mode real time ultrasonography was performed weekly for diagnosis of follicular cyst. Results showed nonsignificant increase in mean DMI (1.86±0.12 kg vs 1.79±0.12 kg per 100 kg body weight) and overall body weight (416.76±10.24 kg vs 411.33±11.07 kg) in treatment group compared to control group. Plasma NEFA concentrations were lower in treatment group as compared to control (329.42±29.08 μmol/L vs 407.05±15.68 μmol/L). Plasma cortisol concentrations were significantly lower in treatment group as compared to control group (4.91±0.68 ng/ml vs 6.89±0.49 ng/ml). In control group, 22.22% cows had follicular cyst on their ovaries whereas no follicular cyst was found in betaine supplemented cows. It can be concluded that supplementation of 50 g betaine/cow/day reduces the incidence of follicular cyst along with reduction in plasma NEFA and cortisol levels.